Globalising Animals <subtitle>Histories for the Anthropocene</subtitle> - Raf De Bont (Journal for the History of Environment and Society, 2022)
Abstract Scholars of globalisation tend to write about humans. They are interested in the movements of (and long-distance connections between) people, products, ideas and money. My contribution, however, explores how a more-than-human history of globalisation could look like. It does so by highlighting the ways in which the globalisation process has changed the interaction between humans and undomesticated animals throughout the twentieth century. First, I probe how infrastructures of globalisation (ranging from railroads to pipelines) have influenced the movements of undomesticated animals. Second, I investigate the ways in which humans have tried to get to grips with these movements – through scientific study, media representations and various management regimes. The contribution concludes by launching the idea that the twentieth century saw a gradually developing ‘world natureculture’. Modernist ambitions of control over non-human life forms largely shaped this development. Yet, I also draw attention to the ideas, practices and technologies that have sought to attune human and non-human movements in a shared choreography. These might offer a useful starting point for rethinking the interaction between human and non-human life forms for the future.